2011
DOI: 10.1044/1058-0360(2011/10-0104)
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Teacher Responsivity Education on Preschoolers' Language and Literacy Skills

Abstract: Although teacher responsivity education is viewed as benefitting children's language and literacy development, the impacts of this type of intervention on children's skills warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 59 publications
1
68
2
6
Order By: Relevance
“…Consistent with the present findings, prior studies have reported that whole class intervention tends to benefit the skills of children entering the year with relatively higher levels of language skill (Cabell et al, in press; Justice et al, 2010). It is reasonable to assume that children with better language skills will be able to take greater advantage of learning opportunities presented to them in the classroom.…”
Section: Implications For Practicesupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the present findings, prior studies have reported that whole class intervention tends to benefit the skills of children entering the year with relatively higher levels of language skill (Cabell et al, in press; Justice et al, 2010). It is reasonable to assume that children with better language skills will be able to take greater advantage of learning opportunities presented to them in the classroom.…”
Section: Implications For Practicesupporting
confidence: 92%
“…Many professional development approaches aimed at improving preschool teacher practice have demonstrated limited success in moving children's early skills forward, particularly the oral language skills of children who are deemed at risk (e.g., Cabell et al, in press; Dickinson et al, 2011). Therefore, even the small effect of MTP on children's skills reported in the present study is meaningful.…”
Section: Implications For Practicementioning
confidence: 99%
“…All videos were included in further analyses. The proportion of timeslots in which participants used each strategy or behaviour was used as the main dependent variable to measure adult interaction behaviour, as used by Cabell et al (2011) in their similar study of LLLI-based training. As shown in Table 3, Friedman's tests showed statistically significant increases in the use of two communication-facilitating strategies: 'uses comments to cue another turn' (χ 2 (2) = 7.00, p = 0.03), and 'looks warm and expectant to encourage interaction' (χ 2 (2) = 7.625, p = 0.022).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, data from 7 to 10 children per classroom (130 in total) were analyzed for the present study. Therefore, the sample of 130 children represents about 44% to 63% of the enrollment within each classroom, which is characteristic of many large-scale studies of child development in early education settings (Cabell et al, 2011; Justice, Kaderavek, Fan, Sofka, & Hunt, 2009). However, it is necessary to acknowledge that the present work makes inferences regarding the relations between classroom age composition and children’s language growth.…”
Section: Methodsmentioning
confidence: 99%